A Ketogenic Diet Improves Cognition and Has Biochemical Effects in Prefrontal Cortex That Are Dissociable From Hippocampus - Hernandez, Abbi R.; Hernandez, Caesar M.; Campos, Keila; Truckenbrod, Leah; Federico, Quinten; Moon, Brianna; McQuail, Joseph A.; Maurer, Andrew P.; Bizon, Jennifer L.; Burke, Sara N. (Frontiers in Aging Neuroscience, 2018)
Age-related cognitive decline has been linked to a diverse set of neurobiological mechanisms, including bidirectional changes in proteins critical for neuron function. Importantly, these alterations are not uniform across the brain. For example, the hippocampus and prefrontal cortex show distinct patterns of dysfunction in advanced age. Because higher cognitive functions require large-scale interactions across prefrontal cortical and hippocampal networks, selectively targeting an alteration within one region may not broadly restore function to improve cognition. One mechanism for decline that the prefrontal cortex (PFC) and hippocampus (HPC) share, however, is a reduced ability to utilize glucose for energy metabolism. Although this suggests that therapeutic strategies bypassing the need for neuronal glycolysis may be beneficial for treating cognitive aging, this approach has not been empirically tested. Thus, the current study used a ketogenic diet (KD) as a global metabolic strategy for improving brain function in young and aged rats. After 12 weeks, rats were trained to perform a spatial alternation task through an asymmetrical maze, in which one arm was closed and the other was open. Both young and aged KD-fed rats showed resilience against the anxiogenic open arm, training to alternation criterion performance faster than control animals. Following alternation testing, rats were trained to perform a cognitive dual task that required working memory while simultaneously performing a bi-conditional association task (WM/BAT), which requires PFC-HPC interactions. All KD-fed rats also demonstrated improved performance on WM/BAT. At the completion of behavioral testing, tissue punches were collected from the PFC for biochemical analysis. KD-fed rats had biochemical alterations within PFC that were dissociable from previous results in the HPC. Specifically, MCT1 and MCT4, which transport ketone bodies, were significantly increased in KD-fed rats compared to controls. GLUT1, which transports glucose across the blood brain barrier, was decreased in KD-fed rats. Contrary to previous observations within the HPC, the vesicular glutamate transporter (VGLUT1) did not change with age or diet within the PFC. The vesicular GABA transporter (VGAT), however, was increased within PFC similar to HPC. These data suggest that KDs could be optimal for enhancing large-scale network function that is critical for higher cognition.